Statistics regarding children in different centres
039-0075-001 July 27th, 1937. IN CAMP JULY 22nd: Boys 476 Girls 197 Children 673 Maestras 68 APPROVED CENTRES: Aldershot 20 Looking for house. Brechfa 50 ? Additional Birmingham II 60 Going 29/7/37 Birkenhead 30 Additional Carshalton 20 ?50 Equipping & Staffing Colwyn Bay 20 Going 29/7/37 Diss 50 Boys. Miss Vulliamy's Camp. Going 31/7/37 Dorking 20 East London 50 Looking for house. Halifax 20 Looking for house. Huddersfield 20 Going 28/7/37 North Shields 20 Going 30/7/37 Sheffield 25 Looking for house. Southampton 30 Staffing and Equipping. 435 NEGOTIATIONS PROCEEDING: Bradford 30 ? Committee being formed Burnley 29 Looking for house. Colchester 20 Very doubtful, hangs fire Dundee 20 Not till September Hull (Tarran Industries) 20 Going 30/7/37 "Hazeldene" Llanelly 20 ? Burton-on-Trent 20 Committee being formed Chelmsford 20 Hanging fire Leicester (Saddington Hall) 25 Nairn 20 Process of getting Committee together Swindon 25 Staffing and Equipment 240 292/946/39/75